Re-evaluation of common carp (Cyprinus carpio L.) housekeeping genes for gene expression studies – considering duplicated genes. Issue 115 (August 2021) - Szczygieł, Joanna; Kamińska-Gibas, Teresa; Petit, Jules; Jurecka, Patrycja; Wiegertjes, Geert; Irnazarow, Ilgiz
Abstract: Quantitative real-time PCR is one of the most widely used techniques for measuring changes in the expression of target transcripts due to its sensitivity, specificity, and cost-effectiveness. However, the essential step that determines appropriate and correct data interpretation is the selection of proper endogenous control genes. Identifying useful reference genes with stable expression is critical for accurate normalization and precise results. Functional divergence of duplicated genes in tetraploid species, like common carp, can complicate the choice for a proper reference gene. In the present study, we determined the expression stability of duplicated genes of 40s, b2m, ef1α, gapdh, g6pd, and odc1 in different tissues of common carp ( Cyprinus carpio L.). Gene expression analysis comprised healthy control fish, fish under bacterial and parasitic infections, and across the early stage of common carp development. Obtained data were compared with the actb gene, which is used widely as a reference in RT-qPCR analysis. The application of the three different algorithms - geNorm, NormFinder, BestKeeper, allowed comparative evaluation of the expression stability of the tested genes. Subsequently, the RefFinder, a web-based tool, was used to rank the examined housekeeping genes comprehensively. We demonstrate variable transcription stability levels in the examined mRNAs as well as differences in expression between paralog gene copies. The 40s, b2m, ef1α and actb genes showed the most stable expression across all physiological conditions and tissues. The gapdh, odc1, and g6pd gene variants demonstrated lower stability. Differences in expression patterns between duplicated genes underline the possibility of functional divergence between them. This aspect should be considered in polyploid species before selecting the reference gene(s). Our study also points on the importance of choice for a reference gene (paralog) when expressing newly identified genes and the spatial expression profile is performed. Subjects: Aquaculture, Molecular Biology, Fish Science. Highlights: The study demonstrates differences in both stability and levels of expression between housekeeping gene duplicates. The evaluation of paralogs as reference genes is crucial in polyploid species. Amplification of paralogs with a single primer pair may lead to misinterpretation of the expression profiles of tested genes.